2012
DOI: 10.1136/bmjqs-2012-000951
|View full text |Cite
|
Sign up to set email alerts
|

Impact of multidisciplinary simulation-based training on patient safety in a paediatric emergency department

Abstract: Simulation training is an effective tool to modify safety attitudes and teamwork behaviours in an ED. Sustaining cultural and behavioural changes requires repeated practice opportunities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
93
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(105 citation statements)
references
References 43 publications
3
93
0
6
Order By: Relevance
“…Possibly relevant are studies that measured the impact of team training in general medical settings, but the results of these studies are mixed. One study in a pediatric emergency room found that team training reduced notable patient safety events [49]. In contrast, a systematic review of interdisciplinary team care interventions identified 30 studies, and found a weak impact on complications of care (reduced in 5 of 10 studies) but generally no impact on length of stay, readmissions, or mortality [50].…”
Section: Discussionmentioning
confidence: 99%
“…Possibly relevant are studies that measured the impact of team training in general medical settings, but the results of these studies are mixed. One study in a pediatric emergency room found that team training reduced notable patient safety events [49]. In contrast, a systematic review of interdisciplinary team care interventions identified 30 studies, and found a weak impact on complications of care (reduced in 5 of 10 studies) but generally no impact on length of stay, readmissions, or mortality [50].…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that approximately 400,000 patients die each year due to preventable adverse events, and between 2 and 4 million adverse events generate serious consequences to patient health without leading to death. When compared to adults, hospitalized children are three times more likely to suffer injury (2)(3) . In this sense, the World Health Organization (WHO) sought to develop global policies that would improve the care offered in health services, reversing this drastic situation.…”
Section: Introductionmentioning
confidence: 99%
“…A avaliação da atividade foi positiva, refletindo bom aproveitamento e possibilitando melhor integração da equipe multidisciplinar. Esta é uma potencial vantagem da simulação in situ comparada à simulação no centro de simulação: a possibilidade de treinar equipes que atuam juntas em seu ambiente de trabalho 4,12 .…”
Section: Discussionunclassified
“…Esse relato demonstrou grande risco associado à prática médica e recomendou treinamento em equipes com uso de simulação como possível ferramenta para minimizar esses eventos. Em estudo que avalia o impacto da simulação na segurança do paciente em departamento de emergência pediátrico, Patterson et al 4 demonstraram mudança de atitude da equipe multidisciplinar em relação a eventos adversos e significativa redução desses eventos. O presente estudo relata uma experiência inédita no Brasil: o uso de simulação in situ para treinamento de equipes e identificação de ameaças à segurança latentes em unidade de pronto atendimento.…”
unclassified